Quantifying the role of automatic stabilisers in New Zealand using a macro-simulation approach - Andrew Binning (New Zealand Government, The Treasury, 2024)
Automatic stabilisers are fiscal policy's first line of defence in the face of adverse economic shocks. Automatic stabilisers capture fiscal policy's automatic countercyclical response to the state of the business cycle, and are determined by factors like the progressivity of the tax system, the size of government and the amount of benefit spending that is dependent on recipients' economic circumstances. Built into the system, they do not require legislative action each time they are implemented, meaning they can be deployed relatively quickly. In this paper I investigate the role automatic stabilisers play in stabilising the New Zealand economy across the business cycle. I benchmark current automatic stabilisation policy against different definitions of neutral fiscal policy to determine their contribution to stabilising the economy. I find the standard deviation of GDP could be up to 29% higher in a world without automatic stabilisers. Plausible gains from strengthening automatic stabilisers from current settings are likely to be much smaller. Automatic stabilisers play a larger role when monetary policy is constrained by the lower bound on interest rates or the monetary policy response to inflation and output is weak.
Keywords: H6; H30; E37; E62; 330; automatic fiscal stabilisers; macro-simulation; counter-factual policy simulation